POTENSI DAN KONTRIBUSI ZAKAT, INFAQ DAN SHADAQAH DALAM PENINGKATAN EKONOMI DAN PENDIDIKAN (STUDI KASUS DI WILAYAH KOTA BOGOR) - Muhajirin Muhajirin (Universitas Muhammadiyah Prof Dr Hamka, 2017)
The nature of zakat, infaq and shadaqah is basically the doctrine of mankind (spiritual and moral) which is expected to meet the needs of the muslims and as one of the state revenue. However, infaq and shadaqoh coverage is wider because it includes all good deeds. Zakat, infaq and shadaqah (ZIS) collection techniques at Baznas Bogor city by carrying programs on collection are arranged into five main activities namely: Communicating the activities of Baznas intensively, recruiting new muzakki, echoing ZIS Ramadan, maintaining existing muzakki, and strengthening the structure of UPZ mosque network (FORSIL) and Gebu Cinta. The concept or distribution allocated for students scholarship or based on students achievement but not economically capable, assistance to teachers of Quran, capital assistance for traders either with mudharabah system or over the name of mustahiq. Health assistance and development of da’wah in the ciy of Bogor.